Refugee Return and Social Cohesion - Ruiz, Isabel (World Bank, Washington, DC, 2022)
This paper explores the impact of refugee return on social cohesion using data from Burundi, a country that experienced high levels of repatriation during the 2000s. It uses a nationwide survey conducted in 2015 and relies on geographic features of the communities for identification purposes. The results suggest varying impacts of refugee return on different aspects of social cohesion. The stronger effects, suggest that refugee return has a negative impact on the feeling that community members help each other, could borrow money for emergencies from non-household members and feeling that the community is peaceful. The estimated impacts on measures of reconciliation, post-conflict justice, trust and participation in community groups are mostly statistically insignificant. The paper also explores how these effects differ across different sub-samples based on ethnic composition, land scarcity and attitudes towards return. The results highlight the possible role of new migration-related societal divisions (i.e. returnees versus stayees) in affecting post-return social cohesion.